The practice of autonomous learning among arabic language learners : a case study at the Centre of Language and Pre-University Academic Development (CELPAD), IIUM - Hussein, Abdul Kadir (Institute of Education, International Islamic University Malaysia, 2012)
This survey study is carried out to investigate the practice of autonomous learning among Arabic language learners in the center of language and pre-university academic development division (CELPAD) (IIUM). Specifically, this quantitative study seeks to answer five main inquiries, namely: (1) Do Arabic language learners in CELPAD practice Autonomous learning of Arabic? (2) Is there any gender difference in the practice of autonomy among CELPAD Arabic language learners? (3) How do CELPAD Arabic language learners perceive their responsibilities for their own language learning? (4) How do CELPAD Arabic language learners perceive their teachers' responsibilities for their learning? And finally, (5) Is there any relationship between CELPAD Arabic language learners' perceptions on their responsibility and their level of autonomy?. Data was gathered through adapted questionnaire from 179 Arabic language learners. Both descriptive and inferential statistics were employed to analyze the data using SPSS software version 6.0. Results revealed that learners seemed to be more inclined to autonomy even though they believe that teachers are more responsible for their learning.More so, the finding revealed that there was no gender difference in their practice of autonomous learning. Moreover, results showed that, learners perceive themselves as responsible learners, however, they still need teachers' intervention in their learning. Nevertheless, there was a significant relationship between learners' perceptions of their learning responsibilities and their autonomy level. Generally, this study provides useful insight that can benefit CELPAD Arabic language teachers as well as curriculum designers. It inferred that there is a need to promote autonomy among learners as it was found that they are ready for this step.